High-performance thermoelectric fabric based on PEDOT:Tosylate/CuI. (December 2021) - Rousti, Anna Maria; Maji, Tanmoy; Drew, Christopher; Kumar, Jayant; Christodouleas, Dionysios C.
Abstract: Fabric-based thermoelectrics can be seamlessly integrated into clothing so they would be ideal to power devices embedded into smart clothing. This study describes the development of thermoelectric fabrics that have their fibers covered with PEDOT:Tosylate and CuI nanocrystals. Several types of fabrics (e.g., cotton, nylon, NYCO, polyester, nomex, modacrylic etc.) have been used in the fabrication of different fabrics PEDOT:Tosylate composites and it was concluded that NYCO (a fabric composed of 50% cotton, 50% nylon) provided the highest thermoelectric performance. The integration of CuI nanocrystals in the NYCO/PEDOT:Tos/CuI composites boosted the thermoelectric power of the composites, almost 8 times compared to NYCO/PEDOT:Tos, to reach a power density equal to 3.68 nW cm −2 (ΔΤ = 12 Κ). A proof-of-concept wearable thermoelectric device that uses four strips of NYCO/PEDOT:Tos/CuI and four monel wires was able to produce up to 70 nW of power when ΔT = 25 K. The device was folded and attached at the edge of an armband (so that one end of each fabric PEDOT:Tos/CuI composite to be in contact with the skin and the other open to environment) and was able to produce 12.4 nW when the armband is worn by a person and the difference between the surface of the skin and the outer side of the device was 8 K. Highlights: High-performance, flexible fabric-based thermoelectric composite can produce 3.68 nW cm −2 (ΔT = 12 K). Addition of CuI nanocrystals into NYCO/PEDOT:Tos fabric composite boost Seebeck coefficient from 68 μV K −1 to 151 μV K −1 . A wearable thermoelectric device based on NYCO/PEDOT:Tos/CuI produce 70 nW when ΔT = 25 K. NYCO fabric provide best results among several types of fabrics.